2022
DOI: 10.3390/ijms23169320
|View full text |Cite
|
Sign up to set email alerts
|

Expression of TXNRD1, HSPA4L and ATP1B1 Genes Associated with the Freezability of Boar Sperm

Abstract: Cryopreservation is associated with increased oxidative stress, which is responsible for sperm damage. We analyzed the effect of cryopreservation on mRNA and protein expression of thioredoxin reductase 1 (TXNRD1), heat shock protein family A (HSP 70) member 4 like (HSPA4L) and sodium/potassium-transporting ATPase subunit beta-1 (ATP1B1) genes in boar sperm with different freezability. Boars were classified as having good and poor semen freezability (GSF and PSF, respectively), according to the assessment of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…The high abundant SPEV-coupled miRNAs also target 107 functional mRNAs in the sperm. The heat shock protein family A member 4 like and eukaryotic translation elongation factor 1 beta 2 targeted by gga-miR-10b-5p and gga-miR-10a-5p, respectively, were highly expressed in hypospermate individuals and were associated with embryonic development ( Selvaraju et al, 2021 ; Mańkowska et al, 2022 ). The DEAD-box helicase 4 is a germline-specific gene and Transglutaminase 4, a prostate-specific gene used as a control gene, are also regulated by gga-miR-10b-5p and gga-miR-10a-5p ( Kim et al, 2015 ; Yu et al, 2016a ).…”
Section: Discussionmentioning
confidence: 99%
“…The high abundant SPEV-coupled miRNAs also target 107 functional mRNAs in the sperm. The heat shock protein family A member 4 like and eukaryotic translation elongation factor 1 beta 2 targeted by gga-miR-10b-5p and gga-miR-10a-5p, respectively, were highly expressed in hypospermate individuals and were associated with embryonic development ( Selvaraju et al, 2021 ; Mańkowska et al, 2022 ). The DEAD-box helicase 4 is a germline-specific gene and Transglutaminase 4, a prostate-specific gene used as a control gene, are also regulated by gga-miR-10b-5p and gga-miR-10a-5p ( Kim et al, 2015 ; Yu et al, 2016a ).…”
Section: Discussionmentioning
confidence: 99%
“…The Ningxiang pigs, classified as an obese-type breed, are renowned for their abundant fat content and excellent meat quality. In this study, we identified genes ZNF280D [41], PLIN1 [42], PAPPA2 [43], SLC5A4 [44], and CABIN1 [45], which were found to be associated with BFT in pigs, and CCPG1 [46], ATP1B1 [47], and CABS1 [16], which demonstrated associations with reproductive performance in boars. Additionally, we identified some genes that simultaneously influence multiple traits.…”
Section: Identification Of Roh Islands Candidate Genes and Qtlmentioning
confidence: 90%
“…However, TXNRD1 should work as a scavenger of ROS by controlling the redox state of oxidized proteins; however, even when the expression was higher in the cryopreserved group, the potential cryo-induced oxidative damage may have decreased the quality of frozen boar spermatozoa after thawing. The ATP1B1 gene may be used as a cryotolerance marker of spermatozoa to cold shock because a significant loss of mRNA expression as well as ATP1B1 protein in fresh prefreeze samples predicts reduced freezability [ 62 ].…”
Section: Genetic Markersmentioning
confidence: 99%